Knowledge, attitudes and behaviours of nurses about antibiotic use and antibiotic resistance in Oman - Zainab Said Al-Hashimy; Barbara R. Conway; Sayer Al-Azzam; Reema Karasneh; Halima Ali Rashid Al Kiyumi; Stuart E. Bond; Kelly Atack; Raneem Saed Nofal; Mamoon A. Aldeyab (PLoS ONE, 2026)
Background Antimicrobial resistance (AMR) is a significant global health challenge, with organizations worldwide emphasizing the importance of addressing inappropriate antibiotic use and resistance. The aim of this study was to investigate nurses’ knowledge, attitudes, and behaviour on antibiotic use and resistance in Oman. Methods This cross-sectional study used a questionnaire designed by the European Centre for Disease Prevention and Control, which was distributed to nurses working in Oman’s Ministry of Health. Results A total of 424 nurses responded to the survey. A total of 64.2% and 48.8% of the respondents accurately acknowledged the lack of efficacy of antibiotics against viruses and the common cold, respectively. Nevertheless, a significant majority of 93% of participants were able to provide accurate responses regarding excessive use of antibiotics and associated adverse effects. Out of the surveyed nurses, 59% demonstrated awareness of the Oman National Action Plan on antibiotic resistance. Of those who responded, 54.7% wanted to know which antibiotics are used for specific medical conditions, 52.1% wanted to know more about antibiotic resistance, 42% wanted to learn about the proper usage of antibiotics, and 30% were interested in the links between humans, animals, and environmental health. Conclusion The study’s results should be used to enhance education and increase nurses’ capabilities and understanding regarding antibiotic use and antibiotic resistance. Strengthening capabilities, opportunities, and motivation is essential to empower nurses as frontline contributors in the global fight against antibiotic resistance.